Study design and rationale of the 'Balloon-Expandable Cobalt Chromium SCUBA Stent versus Self-Expandable COMPLETE-SE Nitinol Stent for the Atherosclerotic ILIAC Arterial Disease (SENS-ILIAC Trial) Trial': study protocol for a randomized controlled trial. Issue 1 (December 2016) - Choi, Woong; Rha, Seung; Choi, Cheol; Kim, Eung; Oh, Dong; Cho, Yoon; Park, Sang; Lee, Seung; Hur, Ae; Ko, Young; Park, Sang; Kim, Ki; et al.
Abstract Background The self-expandable COMPLETE™ stent (Medtronic) has greater elasticity, allowing it to regain its shape after the compression force reduces, and has higher trackability, thus is easier to maneuver through tortuous vessels, whereas the balloon-expandable SCUBA™ stent (Medtronic) has higher radial stiffness and can afford more accurate placement without geographic miss, which is important in aortoiliac bifurcation lesions. To date, there have been no randomized control trials comparing efficacy and safety between the self-expanding stent and balloon-expandable stent in advanced atherosclerotic iliac artery disease. Methods/design The purpose of our study is to examine primary patency (efficacy) and incidence of stent fracture and geographic miss (safety) between two different major representative stents, the self-expanding nitinol stent (COMPLETE-SE™) and the balloon-expanding cobalt-chromium stent (SCUBA™), in stenotic or occlusive iliac arterial lesions. This trial is designed as a prospective, randomized, multicenter trial to demonstrate a noninferiority of SCUBA™ stent to COMPLETE-SE™ stent following balloon angioplasty in iliac arterial lesions, and a total of 280 patients will be enrolled. The primary end point of this study is the rate of primary patency in the treated segment at 12 months after intervention as determined by catheter angiography, computed tomography angiography, or duplex ultrasound. Discussion The SENS-ILIAC trial will give powerful insight into whether the stent choice according to deployment mechanics would impact stent patency, geographic miss, or stent fracture in patients undergoing stent implantation in iliac artery lesions. Trial registration National Institutes of Health Clinical Trials Registry (ClinicalTrials.gov identifier:NCT01834495 ), registration date: May 8, 2012